Regional inequality and convergence in Europe, 1995 - 2005 - Arne Melchior (Center for Social and Economic Research (CASE), 2008)
The paper presents new results on within-country regional inequality in per capita income for 36 countries during 1995-2005; focusing on Europe but with some non-European countries included for comparison. In 23 of the 36 countries there was a significant increase in regional inequality during the period, and in only three cases there was a reduction. Regional inequality increased in all countries of Central and Eastern Europe, while for most Western European countries there was little change. For the EU-27 as a whole, there was a modest increase in within-country regional inequality, but convergence across countries. The latter effect was quantitatively more important, so on the whole there was income convergence in the EU-27, especially after 2000. Regional inequality is particularly important for some large middle-income countries such as China, Russia and Mexico. In such countries there may however be considerable price differences across regions, and the use of common price deflators for the whole country may lead to a biased assessment of regional inequality.
Keywords: R12; O18; 330; Income distribution; regional inequality; economic growth and convergence; European integration; Regionale Einkommensverteilung; Regionales Wachstum; Räumliche Verteilung; Wirtschaftliche Konvergenz; Europäische Integration; Europa; Welt